Solid waste management critical issues for developing countries - Thomas-Hope, Elizabeth M.; International Conference on Solid Waste Management (1995- ) 1995 Kingston, Jamaica). (Kingston, Jamaica Canoe Press, University of the West Indies, 1998)
"This volume presents a collection of papers which, with perspectives from Africa and the Caribbean, raise critical issues in the management of solid waste. It is intended to offer a basis for discussion among the wide range of disciplines and sectors involved in solid waste management and suggest directions for future work in the theoretical and practical dimensions of the challenge with which developing countries are confronted"--Back cover.
Waste management problems in developing countries / Geoffrey Blight and Chuma Mbande -- The community as a resource for solid waste management / Mark Figueroa -- Solid waste: its implications for health / Milton Pinnock -- The pollution potential for waste: a comparison of poor and wealthy communities in South Africa / Jonathan Shamrock -- Heavy metal contamination of a wetland area in east Trinidad / Isaac Bekele et al. -- Solid waste management and environmental education in the school curriculum / Marceline Collins-Figueroa -- An overview of solid waste management in Barbados / Jeffery Headley -- Solid waste management: regulations and related policy issues in Jamaica / Mearle Barrett -- The management of solid waste in Botswana / Geoffrey Blight -- Solid waste management and its environmental impact in Kenya / Gladys Mungai -- The effect of the method of household containment on solid waste management / Ian Gage -- Options for solid waste management in the agroprocessing industry / Velva Lawrence -- The reception and disposal of ship-borne waste: legal and administrative issues / Ludlow Stewart -- The environmental impact of incineration on island nations / Clyde Lettsome -- Landfills: the new generation / Alejandro Gonzalez -- A screening process for the evaluation of sanitary landfill sites in Jamaica / Basil Fernandez -- Landfill siting and design / Walling Whittaker -- Riverton City dump: evaluation of a Jamaican landfill site / Earl D. Wright -- Remedial strategies for the Riverton City landfill / Robert B. Garner, Steven M. Hamilton and Larry E. Ruiz -- An environmentally sustainable waste management strategy for the Caribbean in light of Canada's experience / G. Steve Hart -- An integrated approach to sustainable solid waste management / Shannon Clagget, Stewart Hattie and Keith Watson.
"Based on papers originally presented at the First International Conference on Solid Waste Management, Kingston, Jamaica, September 1995"--Page vii.
Includes bibliographical references and index.
Keywords: Refuse and refuse disposal -- Environmental aspects -- Developing countries -- Congresses; Factory and trade waste -- Environmental aspects -- Developing countries -- Congresses; Sanitary landfills -- Environmental aspects -- Developing countries -- Congresses; Pollution -- Developing countries -- Congresses; Conference papers and proceedings